Evaluation of Some Heavy Metals around the Municipal Solid Waste Disposal Area in Halabja City –Kurdistan Region of Iraq - Muhammad, Sherko A.; H.Karim, Salar (Sulaimani Journal for Pure and Applied Sciences, 2016)
Handling and disposal of solid waste can be a major environmental problem in developing countries. In Kurdistan region of Iraq solid waste is not treated and managed properly. It is only collected from the households and disposed on the outskirts of the cities as a pile of garbage nearby the agricultural areas, sometime it is burnt or partially dumped. The samples were collected monthly starting from May to December 2012 including ground and surface water, soil and wheat around the solid waste disposal area. Heavy metal and metalloid concentrations measured for Zn, As, Cd, Fe, Pb and Ni were ( 0.002 – 0.012 ) mg.l-1, ( 0.01 – 0.097 ) mg.l-1, ( 0.002 – 0.003 ) mg.l-1, ( 0.011- 0.079 ) mg.l-1, ( 0.035 – 0.051 ) mg.l-1and ( 0.004 -0.015 ) mg.l-1 for ground water respectively, while (0.003 - 0.009 ) mg.l-1, ( 0.05 – 0.16 ) mg.l-1, ( 0.002 – 0.004 ) mg.l-1, ( 0.051 – 0.171 ) mg.l-1, ( 0.04 – 0.044 ) mg.l-1, ( 0.021 – 0.022 ) mg.l-1 for surface water respectively. However, As and Pb concentration were found to be higher than the permissible values recommended by WHO for drinking water quality while the rest were below the safe limits. The concentrations of heavy metals and metalloids were found in order of Mn> Zn>Cu >Ni> Pb>Cr>As> Cd ( 987 - 1187 mg.kg-1, 225.03 – 915.3mg.kg-1 , 232.8- 301.1 mg.kg-1, 150.4 – 192.2 mg.kg-1, 76.71 - 193.1 mg.kg-1, 142.2 – 173.1 mg.kg-1, 14.23 – 20.15 mg.kg-1and 2.317 – 5.712 mg.kg-1 ) which exceed the European union standard for Ni, Zn, Cr, Cd, Mn, Cu, while Pb and As were found to be within the range of all trace elements for agricultural soils. The range for trace elements for wheat samples were 115 mg.kg-1 for Zn, 0.0313 mg.kg-1 for As, 1.2 mg.kg-1 for Cd, 2.1 mg.kg-1 for Pb, 1.19 mg.kg-1 for Ni and 0.058 mg.kg-1 for Cr.
Keywords: Halabja Solid wasteEvaluation of someheavy metalsMunicipal Solid WasteDisposal,Effects on the HumanHealth